Digital Contracts: Legal Protection and Validity of Agreements (Universitas Terbuka, 2025)
The Covid-19 pandemic has changed life inextricably linked to digitalization, made it a crucial part of human life. Known as the era of digital transformation. Digital transformation has become a phenomenon that has significantly transformed the global business landscape, including the shift from paper-based to paperless data. It’s provided all kinds of convenience to the global community, resulting in faster daily activities. However, various problems have arisen. How is the legal protection afforded to the parties in creating digital contracts? Can these contracts serve as the basis for authenticating the parties' agreements? This study aims to analyze the opportunities, challenges, and innovation strategies required for companies to address changes triggered by advances in digital technology. This study uses a library research method derived from various digital Open Source sources and expert theories. This study uses a qualitative method with case study analysis of companies that have successfully and unsuccessfully adapted to digital transformation. The findings of this study indicate the need for a contract model within the existing legal framework to guarantee legal protection, which is a manifestation of legal transformation in Indonesia.